A survey of P2P content sharing in MANETs. (January 2017) - Shah, Nadir; Abid, S.A.; Qian, Depei; Mehmood, Waqar
Abstract: Recently, several approaches have been proposed for Peer-to-peer (P2P) content/file sharing in mobile ad hoc networks (MANETs). In this article, we apprise a comprehensive survey of researches related to P2P overlay networks for sharing the content at the application layer in MANETs. We compare and contemplate the features, vitality, and vulnerability of these approaches and highlight indispensable research challenges that are imperative to address and will have substantial vantages. The fallout of the analysis would serve as a substantial guide for anyone willing to delve into research on the topic of P2P overlay over MANETs.